Social Media Engagement & Listening - Nestor Tyrovouzis (Journal Of Global Strategic Studies, 2025)
Until now, academic literature has described public diplomacy and strategic communication as two distinct; analogous; connected; occasionally conflicting or incompatible; constitutive or subordinate to the other concepts. Still, their correlation has yet to be clearly defined. Nonetheless, a strategic approach to public diplomacy communication efforts would provide PD actors with the necessary tools to better assess and evaluate input, output and the impacts and outcomes of their campaigns and policies. This article identifies four communication components with strategic value in public diplomacy: the Message, the Medium, Engagement and Listening. These components can fulfil both relational and strategic functions and provide the basis for a successful implementation of essential strategic tools, such as audience analysis, message strategy, channel choice, program assessment and measurable goals and objectives. The suggested approach could serve as a starting point for enhancing the effectiveness of applied public diplomacy or for developing new public diplomacy strategies, that would serve better the interests of both governments and their foreign audiences.